(untitled) (The Research of Medical Science Review, 2024)
The study was conducted to assess the correlation of smartphone addiction with sleep quality and mental health. It's a cross-sectional study that investigated smartphone addiction, sleep quality, and mental health of 176 BS Nursing students of BScN final year in Islamabad. The data was collected through an organized approach using consent from participants. It used simple random sampling in the research process. The Smartphone Addiction Scale Short Version (SAS-SV), the Pittsburgh Sleep Quality Index (PSQI), and DASS-21 were applied in this study. Statistical analysis was conducted using SPSS 27 and MSExcel 365. Extended smartphone use seems to have significant impacts on users' physical, mental health, as well as sleep. It is concluded, from this study, that smartphone addiction founded to have a negative impact on both mental and physical health thereby affecting the quality of sleep as well.